2013
DOI: 10.1007/s13280-013-0387-5
|View full text |Cite
|
Sign up to set email alerts
|

Novel Organisms: Comparing Invasive Species, GMOs, and Emerging Pathogens

Abstract: Invasive species, range-expanding species, genetically modified organisms (GMOs), synthetic organisms, and emerging pathogens increasingly affect the human environment. We propose a framework that allows comparison of consecutive stages that such novel organisms go through. The framework provides a common terminology for novel organisms, facilitating knowledge exchange among researchers, managers, and policy makers that work on, or have to make effective decisions about, novel organisms. The framework also ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 45 publications
(58 reference statements)
0
70
0
Order By: Relevance
“…Current scientific divisions between invasion ecology and ecology is resulting in scientific synergies being inadvertently lost. Species naturally colonising novel environments necessarily go through the same stages of introduction, establishment and spread as species introduced by humans, because they are subject to the same barriers of survival, reproduction, dispersal and further range expansion, and therefore are identical from a scientific perspective (Ricklefs 2005;Jeschke et al 2013;Rius and Darling 2014;Yek and Slippers 2014). In terms of understanding the processes, mechanisms, and consequences of colonisation, the means of access to new areas is inconsequential.…”
Section: Artificial Distinctions Don't Aid Sciencementioning
confidence: 99%
“…Current scientific divisions between invasion ecology and ecology is resulting in scientific synergies being inadvertently lost. Species naturally colonising novel environments necessarily go through the same stages of introduction, establishment and spread as species introduced by humans, because they are subject to the same barriers of survival, reproduction, dispersal and further range expansion, and therefore are identical from a scientific perspective (Ricklefs 2005;Jeschke et al 2013;Rius and Darling 2014;Yek and Slippers 2014). In terms of understanding the processes, mechanisms, and consequences of colonisation, the means of access to new areas is inconsequential.…”
Section: Artificial Distinctions Don't Aid Sciencementioning
confidence: 99%
“…Then we performed descriptive analyses based on data and meta-data extracted from the included articles. These descriptive analyses dealt with bibliographic information (year of publication), taxonomic and geographic coverage, invasion stages (sensu Blackburn et al 2011 andJeschke et al 2013), and finally, impact and management of review and original articles.…”
Section: Analysesmentioning
confidence: 99%
“…Alien species invasions cause a multitude of impacts on environment (Vilà et al 2010, 2011, Jeschke et al 2013, Simberloff et al 2013, Blackburn et al 2014, and socioeconomy (Pimentel et al 2000, Pimentel 2002, Gren et al 2009). In particular, there is evidence for an increasing magnitude of human health impacts by alien species (Kenis and Branco 2010, Vilà et al 2010, Richter et al 2013, Conn 2014, Hulme 2014, Mazza et al 2014, as globalization increases the likelihood for the movement of disease vectors (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the potential risk posed by GE algae depends on their capacity to disperse, establish themselves in wild communities, and persist in the presence of native species. Concerns about ecological and public health impacts arising from escaped mass-cultured GE algae strains have been raised based on comparisons with invasive species [9][10][11][12][13], but never tested experimentally. While there are no cases of GE algae establishing in wild communities described in the literature, examples of invasive aquatic or terrestrial species with significant environmental impacts have been observed [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%